Action leveraging evidence to reduce perinatal mortality and morbidity (ALERT): study protocol for a stepped-wedge cluster-randomised trial in Benin, Malawi, Tanzania and Uganda - Joseph Akuze; Kristi Sidney Annerstedt; Lenka Benova; Effie Chipeta; Jean-Paul Dossou; Mechthild M. Gross; Hussein Kidanto; Bruno Marchal; Helle Mölsted Alvesson; Andrea B. Pembe; Wim van Damme; Peter Waiswa; et al. (BMC, 2021)
Abstract Background Insufficient reductions in maternal and neonatal deaths and stillbirths in the past decade are a deterrence to achieving the Sustainable Development Goal 3. The majority of deaths occur during the intrapartum and immediate postnatal period. Overcoming the knowledge-do-gap to ensure implementation of known evidence-based interventions during this period has the potential to avert at least 2.5 million deaths in mothers and their offspring annually. This paper describes a study protocol for implementing and evaluating a multi-faceted health care system intervention to strengthen the implementation of evidence-based interventions and responsive care during this crucial period. Methods This is a cluster randomised stepped-wedge trial with a nested realist process evaluation across 16 hospitals in Benin, Malawi, Tanzania and Uganda. The ALERT intervention will include four main components: i) end-user participation through narratives of women, families and midwifery providers to ensure co-design of the intervention; ii) competency-based training; iii) quality improvement supported by data from a clinical perinatal e-registry and iv) empowerment and leadership mentoring of maternity unit leaders complemented by district based bi-annual coordination and accountability meetings. The trial's primary outcome is in-facility perinatal (stillbirths and early neonatal) mortality, in which we expect a 25% reduction. A perinatal e-registry will be implemented to monitor the trial. Our nested realist process evaluation will help to understand what works, for whom, and under which conditions. We will apply a gender lens to explore constraints to the provision of evidence-based care by health workers providing maternity services. An economic evaluation will assess the scalability and cost-effectiveness of ALERT intervention. Discussion There is evidence that each of the ALERT intervention components improves health providers' practices and has modest to moderate effects. We aim to test if the innovative packaging, including addressing specific health systems constraints in these settings, will have a synergistic effect and produce more considerable perinatal mortality reductions. Trial registration Pan African Clinical Trial Registry ( www.pactr.org ): PACTR202006793783148. Registered on 17th June 2020.